Severe forms of food allergy - Emanuel Sarinho; Maria das Graças Moura Lins
Abstract Objectives: To guide the diagnostic and therapeutic management of severe forms of food allergy. Data sources: Search in the Medline database using the terms "severe food allergy," "anaphylaxis and food allergy," "generalized urticaria and food allergy," and "food protein-induced enterocolitis syndrome" in the last ten years, searching in the title, abstract, or keyword fields. Summary of data: Food allergy can be serious and life-threatening. Milk, eggs, peanuts, nuts, walnuts, wheat, sesame seeds, shrimp, fish, and fruit can precipitate allergic emergencies. The severity of reactions will depend on associated cofactors such as age, drug use at the onset of the reaction, history and persistence of asthma and/or severe allergic rhinitis, history of previous anaphylaxis, exercise, and associated diseases. For generalized urticaria and anaphylaxis, intramuscular epinephrine is the first and fundamental treatment line. For the treatment in acute phase of food-induced enterocolitis syndrome in the emergency setting, prompt hydroelectrolytic replacement, administration of methylprednisolone and ondansetron IV are necessary. It is important to recommend to the patient with food allergy to maintain the exclusion diet, seek specialized follow-up and, in those who have anaphylaxis, to emphasize the need to carry epinephrine. Conclusion: Severe food allergy may occur in the form of anaphylaxis and food-protein-induced enterocolitis syndrome, which are increasingly observed in the pediatric emergency room; hence, pediatricians must be alert so they can provide the immediate diagnosis and treatment.